MEMBANGUN KEUNGGULAN KOMPETITIF LEMBAGA PENDIDIKAN MELALUI STRATEGI DIVERSIFIKASI - Safira Putri Sukandar; Siti Samroh; Devia Febriani (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse diversification strategies as an effort to build competitive advantage in educational institutions. Amidst the challenges of globalisation and competition between institutions, strategies are needed to improve the competitiveness and sustainability of educational institutions. Diversification, whether related or unrelated, is one strategic solution to reduce dependence on a single source of funding and encourage innovation in educational services. This study employs a literature review method by examining various scientific sources and relevant documents. The analysis reveals that the implementation of diversification strategies enables educational institutions to expand their service reach, increase value added, and strengthen their position in the competitive landscape. Diversification carried out in a planned manner can enhance efficiency, productivity, and sustainability of educational institutions in the long term.